DYNAMICS OF AGRICULTURAL MACHINERY MECHANISMS WITH SIGNIFICANT PARAMETER SPREAD DURING PRODUCTION - Victor P. Zharov (Advanced Engineering Research, 2011)
The technique for calculating the dynamics of link-lever mechanisms of the agricultural machinery, whose inertial forces due to significant parameter spread during production occur at random, is offered.